Why Should I Trust Your Code? - DELIGNAT-LAVAUD, ANTOINE; FOURNET, CÉDRIC; VASWANI, KAPIL; CLEBSCH, SYLVAN; RIECHERT, MAIK; COSTA, MANUEL; RUSSINOVICH, MARK (Communications of the ACM, 2024)
The article looks at confidential computing (CC), an approach to addressing the problem of maintaining the confidentiality and security of data kept and processed in the cloud. It discusses protocols and approaches that can be used to verify the trustworthiness of code that is used within a trusted execution environment (TEE).